Design of a scandium-integrated MOF hybrid hydrogel for simultaneous dye adsorption and antibacterial activity - Aseeri, Abdullah A.; Faez Sead, Fadhil; Altalbawy, Farag M. A.; Yousif, Nawfal; Salih Sahib, Ahmed; Saad Abdulali, Zahraa; Alwan, Mariem; Jawad, Mahmood; Mushtaq, Hiba; Smerat, Aseel (Frontiers in Chemistry, 2025)
In this study, a novel hybrid hydrogel incorporating a scandium-based metal-organic framework (scandium-integrated MOF-hydrogel hybrid) was developed using scandium nitrate, 1,4-naphthalenedicarboxylic acid, oxidized pectin, and chitosan. The synthesized scandium-integrated MOF-hydrogel hybrid demonstrated remarkable dual-functionality in both the adsorption of hazardous dye pollutants and the inhibition of pathogenic bacteria commonly found in wastewater. Characterization of the scandium-integrated MOF-hydrogel hybrid was performed using FT-IR, XRD, SEM, EDAX, CHNO elemental, BET, and XPS analyses, confirming successful MOF integration and a porous, reactive surface. Adsorption experiments showed significant uptake capacities for phenol red and Congo red dyes, reaching up to 40 mg and 60 mg under different physicochemical conditions, including variations in pH, temperature, adsorbent dose, and contact time. Antibacterial assessments against four wastewater-derived bacterial strains revealed minimum inhibitory concentrations ranging from 2 to 64 μg/mL and minimum bactericidal concentrations from 4 to 128 μg/mL. These results highlight the hydrogel’s potential as a multifunctional material for simultaneous pollutant removal and microbial decontamination in wastewater treatment systems.